2017
DOI: 10.1007/s40744-017-0053-7
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Examination, Ultrasound and MRI Imaging of The Painful Elbow in Psoriatic Arthritis and Rheumatoid Arthritis: Which is Better, Ultrasound or MR, for Imaging Enthesitis?

Abstract: IntroductionThe purpose of the current study was to examine the painful elbow, and in particular enthesitis, in psoriatic arthritis (PsA) and rheumatoid arthritis (RA) using clinical examination, ultrasonography (US) and magnetic resonance imaging (MRI).MethodsPatients with elbow pain (11 with PsA and 9 with RA) were recruited. Clinical examination, US and MRI studies were performed on the same day. For enthesitis, the common extensor and flexor insertions and the triceps insertion were imaged (20 patients, gi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 21 publications
0
17
0
1
Order By: Relevance
“…Several studies have found that enthesophytes are more likely to show on US than on MRI. 10,11 The patient shown in Figure 4 is a 34-year-old female runner presenting with ITB/TFL tendinosis. In addition to the thickening and hypoechogenicityof the ITB origin ( Figure 4A), US focused on the focally tender area revealed enthesophyte formation.…”
Section: Enthesophyte Formationmentioning
confidence: 99%
“…Several studies have found that enthesophytes are more likely to show on US than on MRI. 10,11 The patient shown in Figure 4 is a 34-year-old female runner presenting with ITB/TFL tendinosis. In addition to the thickening and hypoechogenicityof the ITB origin ( Figure 4A), US focused on the focally tender area revealed enthesophyte formation.…”
Section: Enthesophyte Formationmentioning
confidence: 99%
“…Might we improve the accuracy of our examinations for this clinical feature in PsA? We have previously suggested that if swelling, as well as tenderness, is present at the enthesis then it is more likely to be associated with US-demonstrated enthesitis 8 . However, swelling is infrequently seen at the enthesis, and is hard to detect at entheses around the shoulder, pelvis, and knee, particularly if the person is obese.…”
Section: Rheumatologymentioning
confidence: 99%
“…However, swelling is infrequently seen at the enthesis, and is hard to detect at entheses around the shoulder, pelvis, and knee, particularly if the person is obese. I have also advocated stressing the enthesis mechanically, by opposing the appropriate muscle contraction, to improve the specificity of clinical examination 8 . This is easy to do at the lateral epicondyle of the humerus, the insertion of supraspinatus, the quadriceps, and at the Achilles, but less easy to do elsewhere and especially if the insertion is purely ligamentous.…”
Section: Rheumatologymentioning
confidence: 99%
“…At present, the frequently used methods for early detection and diagnosis of RA are magnetic resonance imaging, ultrasound and serological examination (including rheumatoid factor, anti-cyclic citrullinated peptide, etc). Be that as it may, there are con nements of these techniques, so the exactness and accuracy is not high [5,6] . Computed tomography and X-rays can only detect lesions in its advanced stage, but do not detect early impairment.…”
Section: Introductionmentioning
confidence: 99%